A Preliminary Assessment of the Reproductive Performance of Nilotic Bucks under Intensive Management in the Semi-arid Climate of Khartoum - Adam, Ahmed Abdel Gadir; Atta, Muzamil (University of Khartoum Journal of Agricultural Sciences, 2023)
Three Nilotic bucks were fed sorghum-based diet and three molasses-based diets to examine the effect of nutrition and seasons in Khartoum (Sudan) on the scrotal circumference, sexual behaviour and semen quality. Reaction time was recorded in seconds from introduction to a goat in oestrus until ejaculation into an Artificial Vagina (AV). The scrotal circumference was measured around the width of the two testicles once every month. Semen was collected by an AV at weekly intervals. Semen characteristics examined were volume of the ejaculate, spermatozoa motility and concentration. Although the Nilotic bucks did not have a period of sexual quiescence, they had an active mating season starting at the beginning of autumn as indicated by the improved semen quality and reaction time (22.8 and 17.0 sec in autumn and winter as compared to 72.3 sec in summer). Testicular circumference reached its maximal size at the beginning of autumn (20.17 cm), remained at this level until mid-winter, and then declined thereafter and reached its minimal value during the next summer (17.08 cm). The season affected all semen characteristics examined and the best semen was obtained in autumn and winter. However, the magnitudes of these seasonal effects may not be sufficient to prevent the bucks from being used for breeding